Concise Review: Current Status and Future Directions on Research Related to Nonalcoholic Fatty Liver Disease. (13th July 2016) - Wruck, Wasco; Graffmann, Nina; Kawala, Marie‐Ann; Adjaye, James
Abstract: Considered a feature of the metabolic syndrome, nonalcoholic fatty liver disease (NAFLD), is associated with insulin resistance, type 2 diabetes, obesity and drug toxicity. Its prevalence is estimated at about 30% in western countries mainly due to sedentary life styles and high fat diets. Genome‐wide association studies have identified polymorphisms in several genes, for example, PNPLA3, and TM6SF2 which confer susceptibility to NAFLD. Here, we review recent findings in the NAFLD field with a particular focus on published transcriptomics datasets which we subject to a meta‐analysis. We reveal a common gene signature correlating with the progression of the disease from steatosis and steatohepatitis and reveal that lipogenic and cholesterol metabolic pathways are main actors in this signature. We propose the use of disease‐in‐a‐dish models based on hepatocyte‐like cells derived from patient‐specific induced pluripotent stem cells (iPSC). These will enable investigations into the contribution of genetic background in the progression from NALFD to non‐alcoholic steatohepatitis. Furthermore, an iPSC‐based approach should aid in the elucidation of the function of new biomarkers, thus enabling better diagnostic tests and validation of potential drug targets. Stem Cells 2017;35:89–96 Abstract : Investigating the progression of nonalcoholic fatty liver disease (NAFLD). The progression of non‐alcoholic fatty liver disease (NAFLD) to non‐alcoholic steatohepatitis (NASH) still needs to be further elucidated to enable better non‐invasive diagnosis and therapies. Here, we review recent findings in this field and propose a multi‐omics approach based on liver biopsies, serum samples and induced pluripotent stem cells (iPSC)‐differentiated hepatocyte like cell (HLC) models. As a result of a meta‐analysis, we reveal several potential biomarkers correlating with the progression of the disease from steatosis and steatohepatitis. The use of disease‐in‐a‐dish models based on hepatocyte‐like cells derived from patient‐specific induced pluripotent stem cells will enable investigations into the genetic background in the progression from NALFD to NASH. Additionally, an iPSC‐based approach will support the assessment of potential biomarkers with the goal of achieving better diagnostic tests and validation of potential drug targets.